Understanding the Meaning of Liberalism from the Maudhu'i Interpretation Perspective in the Qur'an - Jaisyi Aozora Tawazun; Kamiilah Fathiyyah; Khairul Anam (Educational Foundation for Qur'anic Exegesis and Hadith Studies (Yayasan Pendidikan Tafsir Hadis), 2023)
Liberalism is an epistemological ideology that aims to promote social progress and expand the boundaries of individual freedom. Humans are free to think as they please and behave as they please. However, the freedom in question is responsible because a liberal social order cannot be formed without a responsible mindset. A liberal social order cannot be formed without a responsible mindset. The purpose of the author's research is to provide an explanation of Islam and liberalism, the ideas held by liberalism, and mention and explain the verses about liberalism in the Qur'an. This research method uses a qualitative method, which uses reliable and accurate reference sources to strengthen the data taken for material based on literature review. The results of this study are important to understand and apply between Islam and liberalism wisely so as not to contradict Islamic teachings. contradict Islamic teachings. In the Qur'an, some verses emphasize the importance of justice, fair witnesses, and avoiding hatred that can lead to unjust behavior